Synchronic and diachronic readings of Jeremiah scroll: in search of a methodology for Jeremianic studies Part II - Yan, Anderson (Vox Scripturae - Revista Teológica Internacional, 2017)
Whilst part I focused mainly on diachronic approaches to Jer, part II aims to emphasize synchronic aspects of Jer, considering when the earliest period would be in which Jeremiah is available as a complete narrative. The author uses narrative criticism with some modern adaptation to the canonical method, giving importance to the coexistence of the oral tradition with textual traditions within communities.